Combining semi-supervised and active learning to recognize minority senses in a new corpus - Cardellino, Cristian Adrián; Teruel, Milagro; Alonso i Alemany, Laura (2021)
Ponencia presentada en la 24th International Joint Conference on Artificial Intelligence. Workshop on Replicability and Reproducibility in Natural Language Processing: adaptive methods, resources and software. Buenos Aires, Argentina, del 25 al 31 de julio de 2015.